2018
DOI: 10.1111/cdev.13157
|View full text |Cite
|
Sign up to set email alerts
|

Interwealth Contact and Young Children's Concern for Equity

Abstract: This study examined young children's contact with individuals of high‐wealth and low‐wealth backgrounds and their behavior toward peers of these backgrounds in a resource distribution task. The sample included 72 ethnically diverse higher income children (Mage = 6.68 years, SD = 0.98 years). Contact with individuals of low‐wealth backgrounds (interwealth contact) affected children's behavior indirectly, through social‐cognitive reasoning processes. The more interwealth contact children reported, the more likel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 32 publications
0
22
0
1
Order By: Relevance
“…One limitation of the present research is that we relied on samples from relatively homogenous contexts (i.e., University affiliated museums, a college campus, and Amazon’s Mechanical Turk), and we did not measure participants’ own SES or experiences with inequality, both of which have been shown to influence children’s social cognition (see Elenbaas, ). One possibility is that children from contexts marked by severe inequality, and who are themselves high‐status, may be particularly motivated to endorse hypodescent as a means to protect their ingroup from the lower status outgroup.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One limitation of the present research is that we relied on samples from relatively homogenous contexts (i.e., University affiliated museums, a college campus, and Amazon’s Mechanical Turk), and we did not measure participants’ own SES or experiences with inequality, both of which have been shown to influence children’s social cognition (see Elenbaas, ). One possibility is that children from contexts marked by severe inequality, and who are themselves high‐status, may be particularly motivated to endorse hypodescent as a means to protect their ingroup from the lower status outgroup.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding social context, Pauker, Xu, Williams, and Biddle () found that children from regions marked by relatively high levels of racial inequality (e.g., Massachusetts) were more likely to associate race with social status than were children from regions with less inequality (e.g., Hawaii; see also Olson, Shutts, Kinzler, & Weisman, , on race‐status associations among children in a high inequality context). Similarly, Elenbaas () found that children with greater exposure to resource inequality were more likely to rectify it, suggesting a greater concern for and awareness of inequality. Collectively, these studies document extensive variation in the extent to which children associate race with status differences.…”
Section: The History Of Hypodescent In the United Statesmentioning
confidence: 99%
“…Similarly, cross-SES friendships may encourage children’s fairness reasoning. In one recent study, children from upper-middle-income families who reported more contact with peers from lower-income backgrounds were more likely to reason about differences in access to resources when sharing toys and shared more equitably (Elenbaas, 2019a). Although it is not yet known whether interactions with higher-SES peers have a similar impact on lower-SES children’s reasoning, these results point to how everyday interactions with friends may raise children’s consideration of the immediate consequences of resource disparities.…”
Section: Supporting Complex Reasoning About Social Inequalitiesmentioning
confidence: 99%
“…Evidently, the perception of economic inequality is not the only variable that affects tolerance to inequality and attitudes toward redistribution. Literature has traditionally explained attitudes toward redistribution through personal interest and social values or ideology (Brown-Iannuzzi et al, 2015;García-Sánchez, Van der Toorn, Rodríguez-Bailón, &Willis, 2019;Mijis, 2018;Wu & Chou, 2017), and points out how other variables, like age (Elenbaas, 2019;García-Sánchez et al, 2019), and sex (Lierse, 2019;García-Sánchez et al, 2019), can also have an important influence. We consequently aim to control for these variables when examining the effects of PEIEL.…”
Section: Perceived Economic Inequality In Everyday Lifementioning
confidence: 99%